Development of the skiing specific dynamic balance test - Panjan, A.; Supej, M.; Sarabon, N. (2nd International scientific conference: Exercise and quality of life, Novi Sad. March 24/26th 2011, 2011)
The aim of this report is to present the newly developed skiing specific dynamic balance test and the effect of additional weight bearing on the observed parameters. The test is based on the quantification of precision with which a skier is able to track the predefined dynamics of shifting his/her centre-ofpressure. The task is visual feed-back driven and combines the reference curve and the real-time signal from the force plate. Subject sample included 12 professional Slovene skiers. Each subject underwent a set of three tests (without, half and full body additional weight). High repeatability of the analyzed parameters was observed. A statistically significant effect of the additional loading was present and the mechanisms behind it will be discussed.